2017
DOI: 10.1002/1873-3468.12579
|View full text |Cite
|
Sign up to set email alerts
|

Cesium reversibly suppresses HeLa cell proliferation by inhibiting cellular metabolism

Abstract: The aim of the present study was to investigate the influence of Cs on cultured human cells. We find that HeLa cell growth is suppressed by the addition of 10 mm CsCl into the culture media. In the Cs -treated cells, the intracellular Cs and K concentrations are increased and decreased, respectively. This leads to a decrease in activity of the glycolytic enzyme pyruvate kinase, which uses K as a cofactor. Cs -treated cells show an intracellular pH shift towards alkalization. Based on these results, CsCl presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Although cell proliferation was suppressed by concentrations of 1 mM CsCl and higher, cell viability was not remarkably decreased in the same conditions. The relationship between cell viability and cell proliferation was in good agreement with previously reported data regarding HeLa cells 9) .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Although cell proliferation was suppressed by concentrations of 1 mM CsCl and higher, cell viability was not remarkably decreased in the same conditions. The relationship between cell viability and cell proliferation was in good agreement with previously reported data regarding HeLa cells 9) .…”
Section: Resultssupporting
confidence: 91%
“…We previously reported that Cs suppressed cell proliferation in HeLa cells, the human cervical cancer cell line, in a dose-dependent manner 9) . In the present study, we evaluated the effects of Cs on cell proliferation and migration in murine embryotic fibroblast NIH/3T3 cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to the effect of Cs on cultured cells, we previously reported that CsCl suppresses the proliferation of HeLa cells, murine embryonic fibroblast NIH/3T3 cells [28,29]. When CsCl added to the extracellular space enters the intracellular space, intracellular Cs + concentration will then increase and K + concentration decrease.…”
Section: Introductionmentioning
confidence: 99%
“…potential of this work. Finally, it would also be important to purify phages using methods not involving cesium chloride, given this reagent alters cellular metabolism in ways that might impact T helper polarization, colitis, and cancer (Kobayashi et al, 2017).…”
mentioning
confidence: 99%